Effects of high-intensity interval and moderate-intensity continuous exercise on inflammatory, leptin, IgA, and lipid peroxidation responses in obese males - Souza, Daniel Costa de (2018)
Purpose: To compare the effects of a single high-intensity interval exercise session (HIIE) with amoderate-intensity continuous exercise session (MICE) on the inflammatory profile, IgA levels, and lipid peroxidation in sedentary obese males. Methods: Ten sedentary obese men (age 28.5 ± 2.7 years; BMI 35.9 ± 4.9 kg/m2; body fat 40.6 ± 2.0%) performed three experimental sessions, on separate days with 1 week wash-out period between interventions, according to a randomized order: (1) HIIE: 10 × 60 s at 90% of the HRmax alternated by 60 s of active recovery; (2) MICE: 20min at 70% of the HRmax; (3) Rest—control. Blood and saliva samples were collected before, immediately after and 60min after the end of each session in order to analyse serum levels of cytokines, IgA, and lipoperoxidation markers. Results: Leptin levels decreased immediately after HIIE (P = 0.033) and was different from the MICE (P = 0.025). IFN-g levels were reduced immediately after (P = 0.032) and 60min after HIIE (P = 0.003) compared to baseline, and it also increased IL-4 levels immediately after exercise (P = 0.007) compared to resting values. MICE promoted an increase in IFN-g levels immediately after exercise (P = 0.025) and 60min after exercise (P = 0.004) in relation to baseline. Both exercise conditions increased IL-6 levels up to 60min after exercise (P < 0.05). The IFN-g/IL-4 ratio decreased immediately after (P = 0.002) and 60min after HIIE (P = 0.005) in relation to pre-exercise. No changes were found for IgA-S and TBARS for any of the conditions. Conclusion: A single HIIE session is able to decrease IFN-g/IL-4 ratio, indicating an anti-inflammatory response, without alterations in the function of the mucosal immune systemand lipoperoxidation. On the other hand, a brief session ofMICE induced changes in the pattern of cytokines associated with increased cellular immune function.